Physical literacy and health of Chinese medical students: the chain mediating role of physical activity and subjective well-being - Yang, Xiaoqi; Wang, Miaomiao; Wang, Jiangong; Zhang, Shujie; Yang, Xiaoxia; Zhao, Liangyuan (Frontiers in Public Health, 2024)
Background/objective While Physical Literacy has been highlighted as a determinant in health in recent study, there is a dearth of studies examining its effect on physical health, and there is a little in the way of empirical data linking Physical Literacy to health outcomes. Accordingly, further empirical research is needed to clarify the mechanisms by which Physical Literacy affects physical health. The purpose of this study was to verify the role of medical students’ Physical Literacy on Health-related quality of life as well as to explore the chain mediating role of Physical Activity and Subjective Well-being in it. Methods This study utilized a cross-sectional study design. The Physical Literacy, Health-related Quality of Life, Physical Activity ratings, and Subjective Well-being of students at Shanxi Medical University were all measured using an online survey administered in September 2023. A total of 1968 valid questionnaires were returned. First, descriptive statistics and correlation analysis were performed using SPSS software. Second, PROCESS was used to test the mediating role. Finally, we used structural equation modeling (Amos) to test the model fit. Results There is a significant correlation between all variables. After mediation effects analysis, we found that there were three indirect pathways of physical literacy on health-related quality of life: a single mediating effect of physical activity, a single mediating effect of subjective well-being, and a chained mediating effect of physical activity-subjective well-being. Conclusion The mediating role of physical activity and subjective well-being on the relationship between physical literacy and health-related quality of life has been confirmed. Our research results support the integration of physical literacy into physical education teaching and the modification of curriculum content by physical education teachers as part of efforts to enhance students’ physical activity levels, subjective well-being levels, and overall health. This study provides a new perspective for intervention in improving the health of medical students.